Assessment and selection of management consultants: A comparative cognitive study between small- and large-scale companies. Issue 1 (January 2021) - Van Rossem, Annick Dominique Hortense
Abstract: This paper explores alternative ways of evaluating and ultimately hiring a generalist consultancy for short- and medium-term projects, and how this is shaped by the size of the clients' company. What buying factors do managers of small and large firms have in mind when hiring consultants for their projects? Instead of employing surveys incorporating predefined buying factors based on what the researchers think would be important, a cognitive mapping methodology - the repertory grid technique - is applied to investigate the underlying phenomena. Using the repertory grid technique to draw mental models is a novel research technique within the supply management field. Recent behavioral supply chain management research found the behavior of managers to be critically influenced by mental models: the lenses through which managers perceive, simplify and interpret the world. Results show differences between the buying factors used in small- and large-scale companies: managers of large companies are more 'reputation and outcome-oriented' and managers of small businesses are more concerned with 'how the services are rendered'. However, both constituents stressed the importance of expertise, quality and the relationship between the client and the management consultancy, although the character of such a relationship differed between small- and large-scale firms. Results also point out criteria that managers of small and large companies employ to discriminate between good and poor performing consultancies and to judge service delivery. The practical implications for both companies hiring consultancies and the consultancy companies are discussed. For consultancies, our findings can help tailoring their efforts to a differing clientele when marketing and selling their services. For companies hiring consultancies, fixating too much on particular buying factors may lead to biased decisions. Highlights: A cognitive approach to buying factors when hiring management consultancies. A novel research technique within the supply management field for cognitive mapping: the repertory grid technique. Comparison between participants of small and large companies. Distinction between important buying factors and factors for judging service delivery. Interesting practical implications for both consultancy firms and their clients.